Oral Health Awareness and Status Among Universiti Kebangsaan Malaysia First Year Dental Students - Zamirah Zainal Abidin,; Shahida Mohd Said,; Irma Shida Abu Samah,; Mohd Yufi Ariandi Modh Yusoff, (2005)
The oral health awareness and status among the Universiti Kebangsaan Malaysia first year dental students were studied. Seventy-three subjects underwent two components of assessment: questionnaire assessing oral health awareness and behaviour, and clinical examination of oral health status. Indices used including Plaque, Calculus, Community Periodontal Index for Treatment Needs (CPITN) and total score of Decayed, Missing, Filled and teeth indicated for Extraction (DMFX[T]). More than 90% of the subjects were reported to brush their teeth twice or more daily and used supplemental cleaning tools. They also knew the importance of healthy oral condition, the various causes and prevention of tooth decay and gum diseases. Although 70.3% felt they need dental treatment, the majority (81.9%) visited the dentist only when they feel it is necessary to PDF Created with deskPDF PDF Writer - Trial :: http://www.docudesk.com 2 do so. Clinical examination showed low scores of 0.99 and 0.40 for mean plaque and calculus indices, respectively, while 80.8% of the subjects have mild calculus accumulation. Code 2 of the CPITN Index was the highest (70.3%) among the subjects. The total DMFX was 291, with mean score of 0.14 per subject and the decayed component was the highest (D=186 teeth). These findings suggest that the subjects have acceptable oral health awareness, and also good existing oral health status.